Kv1.3 Channel Up-Regulation in Peripheral Blood T Lymphocytes of Patients With Multiple Sclerosis - Markakis, Ioannis; Charitakis, Ioannis; Beeton, Christine; Galani, Melpomeni; Repousi, Elpida; Aggeloglou, Stella; Sfikakis, Petros P.; Pennington, Michael W.; Chandy, K. George; Poulopoulou, Cornelia (Frontiers in Pharmacology, 2021)
Voltage-gated Kv1.3 potassium channels are key regulators of T-lymphocyte activation by providing the necessary membrane hyper-polarization for calcium influx following immune stimulation. It is noteworthy that an accumulating body of in vivo and in vitro evidence links these channels to multiple sclerosis pathophysiology. Herein we studied the electrophysiological properties, the transcriptional and translational expression of T-lymphocyte Kv1.3 channels in multiple sclerosis, by combining patch-clamp recordings, reverse transcription polymerase chain reaction and flow cytometry on freshly isolated peripheral blood T-lymphocytes from two patient cohorts with multiple sclerosis, as well as from healthy and disease controls. Our data demonstrate that T-lymphocytes in MS, manifest a significant up-regulation of Kv1.3 mRNA, Kv1.3 membrane protein and Kv1.3 current density and therefore of functional membrane channel protein, compared to control groups (p<0.001). Interestingly, patient sub-grouping shows that Kv1.3 channel density is significantly higher in secondary progressive, compared to relapsing-remitting multiple sclerosis (p<0.001). Taking into account the tight connection between Kv1.3 channel activity and calcium-dependent processes, our data predict and could partly explain the reported alterations of T lymphocyte function in multiple sclerosis, while they highlight Kv1.3 channels as potential therapeutic targets and peripheral biomarkers for the disease.